2018
DOI: 10.3390/app8050715
|View full text |Cite
|
Sign up to set email alerts
|

Application of Semiconductor Optical Amplifier (SOA) in Managing Chirp of Optical Code Division Multiple Access (OCDMA) Code Carriers in Temperature Affected Fibre Link

Abstract: The application of a semiconductor optical amplifier (SOA) in an incoherent Optical Code Division Multiple Access (OCDMA) system based on multi-wavelength picosecond code carriers is explored for mitigation of temporal distortion of an OCDMA auto-correlation affected by the temperature induced dispersion changes in a fibre optic transmission link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Detection errors will increase significantly if the MAI is over an acceptable threshold at the decoder. Therefore, the author adopted spectral-amplitude-coding (SAC) [18][19][20] to eliminate the MAI effect. Combining the characteristics of SAC codes and an interference cancellation algorithm known as balanced detection, MAI can be blocked at the receiver.…”
Section: Related Workmentioning
confidence: 99%
“…Detection errors will increase significantly if the MAI is over an acceptable threshold at the decoder. Therefore, the author adopted spectral-amplitude-coding (SAC) [18][19][20] to eliminate the MAI effect. Combining the characteristics of SAC codes and an interference cancellation algorithm known as balanced detection, MAI can be blocked at the receiver.…”
Section: Related Workmentioning
confidence: 99%
“…Ahmed and I. Glesk in Ref. [28]. This paper explores the use of SOAs in the transmitter side of such a system based on multi-wavelength picoseconds code carriers for mitigation of temporal distortion of an OCDMA auto-correlation affected by the temperature induced dispersion changes in a fiber optic transmission link.…”
Section: Special Issue Papersmentioning
confidence: 99%
“…Some studies have reported a novel multiplex technique, namely optical code division multiple access (OCDMA) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. OCDMA employs CDMA techniques in optical fiber communication environments.…”
Section: Introductionmentioning
confidence: 99%
“…Because phase shifts must be identified on a coder spectral response, their entire structure is relatively complex. To improve system performance, some researchers have proposed an intelligently structured receiver to suppress noise effects and a semiconductor optical amplifier (SOA) to mitigate temperature variation effects on links [ 16 , 17 ]. In 2018, Yen et al presented Walsh–Hadamard-code-based OCDMA techniques with moderate security for applications in WOC environments [ 18 ].…”
Section: Introductionmentioning
confidence: 99%